Optimalisasi Pengelolaan Dana Zakat Dalam Pengentasan Kemiskinan Mustahik di Kampung Zakat Terpadu Desa Jambearum Kecamatan Sumberjambe Kabupaten Jember - Rifki Mubarok; Hefni Zein (Fakultas Dakwah UIN KHAS Jember, 2022)
Zakat funds are one of the main sources of state finance in Islam. Zakat is one of the elements used to calculate national income in Islam. Zakat is not a personal matter whose implementation is left only on personal awareness, but zakat is a right and obligation for every Muslim who is able and has met the requirements of Islamic law. The focus of the problems studied in this thesis are: 1). How to optimize the management of zakat funds in the Integrated Zakat Village in alleviating poverty for mustahik? 2). What are the forms of optimizing the management of zakat funds in the Integrated Zakat Village? The aims of this research are: 1). Describes the optimization of the management of zakat funds in the Integrated Zakat Village in alleviating poverty for mustahik. 2). Describes the form of optimizing the management of zakat funds in the Integrated Zakat Village. This research method uses a qualitative approach with a descriptive type. Determination of research subjects using purposive sampling and snowball sampling. Data collection techniques using observation, interviews and documentation. The data analysis in this thesis went through three steps, namely data reduction, data presentation and verification/conclusion. As for the validity of the data using source triangulation and technical triangulation. The results of this study indicate that: 1). In optimizing the management of zakat funds in alleviating poverty for mustahik in the Integrated Zakat Village, the theory of zakat fund management has been used, namely planning, implementation, organization and supervision. Regarding the management of zakat funds, the Integrated Zakat Village has three parts, namely collection, distribution, and utilization. 2). From several forms of optimizing the management of zakat funds, the Integrated Zakat Village is currently only focused on the form of assistance to the poor and needy assistance, and for other forms of assistance it has not been implemented evenly, because there are still several obstacles, such as muzakki who do not understand about their obligations. zakat to clean up his property. In addition, some ASNs do not all deposit their zakat through (UPZ) the Ministry of Religion of Jember Regency, because some of them already have a place to deposit their zakat. Thus, this affects the acquisition of zakat funds that will be collected in the Integrated Zakat Village. Keywords: Management of zakat funds, poverty alleviation.zakat to clean up his property. In addition, some ASNs do not all deposit their zakat through (UPZ) the Ministry of Religion of Jember Regency, because some of them already have a place to deposit their zakat. Thus, this affects the acquisition of zakat funds that will be collected in the Integrated Zakat Village.